The effect of profitability, company size, liquidity, bond age and collateral on bond ratings in banking companies listed on the Indonesia Stock Exchange - M.Fajar Zahrul Fadli; Susanti Dwi Ilhami (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
The only form of funding that a company used to obtain funds was by issuing bonds. This research aims to determine the significance of the effect of profitability, company size, liquidity, bond age, and collateral on bond ratings in banking sector companies listed on the IDX. The data in this research is secondary data obtained from www.idx.co.id and the PT Pefindo website. The total sample was 14 banking sector company bonds for the 2018–2022 period, using a purposive sampling method. The data analysis technique used is a logistic regression analysis test with the IBM SPSS Statistics 26 program. The results of the analysis show that profitability has a significant positive effect on bond ratings. Company size has an insignificant negative effect on bond ratings. Liquidity has a significant positive effect on bond ratings. Bond age has an insignificant positive effect on bond ratings. Collateral has a significant negative effect on bond ratings.